A 'difficult' insect allergy patient: reliable history of a sting, but all testing negative. Issue 4 (August 2015) - Tracy, James M.; Olsen, Jonathan A.; Carlson, John
Abstract : Purpose of review: Few conditions are as treatable as allergy to stinging insects, with venom immunotherapy (VIT) providing up to 98% protection to subsequent stings. The challenge with VIT is not in the treatment, but in the diagnosis. To offer VIT, one must determine a history of a systemic reaction to a stinging insect in conjunction with the presence venom-specific IgE. Current diagnostic methods, although sensitive and specific, are imperfect, and some newer testing options are not widely available. A conundrum occasionally faced is the patient with a reliable and compelling history of a systemic allergic reaction yet negative venom-specific testing. This diagnostic dilemma presents an opportunity to consider possible causes for this diagnostic challenge. Recent findings: Our evolving understanding of the role of occult mast cell disease may begin to help us understand this situation and develop appropriate management strategies. Venom-specific skin testing has long been the cornerstone of the evaluation of venom sensitivity and is often combined with in-vitro assays to add clarity, but even these occasionally may fall short. Exploring novel venom diagnostic testing methods may help to fill in some of the diagnostic gaps. Do currently available venom vaccines contain all the key venom species? Are there enough differences between insect species that we may simply be missing the relevant allergens? What is the significance of the antigenicity of carbohydrate moieties in venoms? What is the role of recombinant venom extracts? Summary: VIT is the definitive treatment for insect allergic individuals. To utilize VIT, identification of the relevant Hymenoptera is necessary. Unfortunately, this cannot always be accomplished. This deficiency can have several causes: a potential comorbid condition such as occult mast cell disease, limitations of currently available diagnostic resources, or testing vaccines with an insufficient coverage of relevant venom allergens. Exploring these potential causes may help to provide important insight into this important diagnostic conundrum. The use of a case report may help clarify this challenge.